An actor–network theory model of property development. Issue 2 (26th July 2018) - Ward, Emily
Abstract : Purpose: The purpose of this paper is to model the property development process from an actor–network theory perspective. The model aims to address the relationship between structure and agency to combine the social and the economic aspects of the property development process. Design/methodology/approach: An inductive methodology was appropriate for this study. Consequently, 12 semi-structured interviews have been carried out with professionals involved in the property development process in central London. Findings: Analysis of the interview transcripts revealed that throughout the development process a developer creates a core actor–network and enrols those required for production. Economic, cultural, legal and political structures influence actions throughout the development process and therefore have the ability to cause disruption. As a result, sub-networks are created to overcome challenges throughout the development process, such as obtaining planning consent. This allows the interests of actors to be aligned or re-aligned so that solutions can be punctualised into the core actor–network. Additionally, structures are affected by actions throughout the property development process. Practical implications: It is recommended that developers measure the extent to which the interests of actors are successfully aligned and re-aligned throughout a developments life cycle, in addition to a developments financial success. The findings are paramount for policymakers and regulators, as it allows them to understand the intricate workings of the development process and so when they regulate or develop policy, they will understand how it will reverberate through the process and recalibrate it, thereby limiting unforeseen consequences. Originality/value: This research has proven valuable given it advances the property development process literature by examining the property development process from an actor–network theory perspective and provides areas for further study.